POLITIK HUKUM MENGENAI PENGATURAN PERBUATAN PELAKU DAN PENGGUNA JASA PROSTITUSI ONLINE DI INDONESIA - Hayana, Fahria (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
This research aims to analyze legal politics regarding the regulation of theactions of perpetrators and users of online prostitution services in Indonesia. The lawsthat regulate include: the 1945 Constitution; Law Number 21 of 2007 concerningEradication of the Crime of Human Trafficking; Law Number 44 of 2008 concerningPornography; Law Number 17 of 2016 concerning Amendments to Law Number 23 of2002 concerning Child Protection. The formulation of the problem in the research is tofind out the regulation of online prostitution in the laws and regulations in Indonesiaand to find out the legal politics regarding the regulation of the actions of perpetratorsand users of online prostitution services in Indonesia.The type of research that will be used in this research is normative juridical,namely research carried out by examining secondary legal materials or research basedon standard rules that have been recorded and discussing legal principles and legalsynchronization.In this case, the Criminal Code does not regulate the punishment of prostitutesand users of online prostitution services, so they cannot be held criminally responsible.If we examine the regulations outside the Criminal Code regarding online prostitution,prostitutes and service users can be charged using Article 45 Paragraph (1) of Republicof Indonesia Law No. 19 of 2016 concerning Amendments to Law Number 11 of 2008concerning Information and Electronic Transactions, however this rule is still generalin nature which regulates prohibitions that violate decency. Prostitution regulations canalso be found in Regional Regulations, but not all regions have or issue RegionalRegulations on Prostitution, so their application is limited to the territory. The legalpolicy that can be taken is by reforming criminal law by synergizing with the draftconcept of the Criminal Code, namely by criminalizing or making rules or regulatingthe provision of criminal threats to prostitutes and users of online prostitution servicesso that they can be held criminally accountable (penalization). The suggestion in thisresearch is that there should be an effort to implement legal politics in accordance withthe basic framework of national legal politics, so that the legal products produced donot conflict with the goals of the state and the basic ideals of forming national law. Theauthor's idea of reform is that sex workers are given rehabilitation, job training andworking capital as an effort to prevent them from returning to commercial sex work.Keywords: Legal Politics, Legal Regulations and Online Prostitution.